The Poetics of Otherness - Hart, J. author. aut Link
XV, 263 p.
Keywords: Using the concept of otherness as an entry point into a discussion of poetry, Jonathan Hart's study explores the role of history and theory in relation to literature and culture. Chapters range from trauma in Shakespeare to Bartolomé de Las Casas' representation of the Americas to the trench poets to voices from the Holocaust.